2017
DOI: 10.1038/ncomms16017
|View full text |Cite|
|
Sign up to set email alerts
|

YAP determines the cell fate of injured mouse hepatocytes in vivo

Abstract: The presence of senescent, transformed or damaged cells can impair tissue function or lead to tumorigenesis; therefore, organisms have evolved quality control mechanisms to eliminate them. Here, we show that YAP activation induced by inactivation of the Hippo pathway specifically in damaged hepatocytes promotes their selective elimination by using in vivo mosaic analysis in mouse liver. These damaged hepatocytes migrate into the hepatic sinusoids, undergo apoptosis and are engulfed by Kupffer cells. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 47 publications
1
37
0
1
Order By: Relevance
“…Interestingly, omega-3 polyunsaturated fatty acids (ω−3 PUFAs) inhibited HSC activation and CCl 4 -induced liver fibrosis by promoting YAP/TAZ degradation [29]. Another recent study demonstrated that YAP activation selectively eliminates damaged hepatocytes by switching cell fate from proliferation to migration/apoptosis in response to cell stresses such as ethanol damage in both liver sinusoidal epithelial cells and hepatocytes [30]. …”
Section: The Hippo Pathway In the Development And Regeneration Of Difmentioning
confidence: 99%
“…Interestingly, omega-3 polyunsaturated fatty acids (ω−3 PUFAs) inhibited HSC activation and CCl 4 -induced liver fibrosis by promoting YAP/TAZ degradation [29]. Another recent study demonstrated that YAP activation selectively eliminates damaged hepatocytes by switching cell fate from proliferation to migration/apoptosis in response to cell stresses such as ethanol damage in both liver sinusoidal epithelial cells and hepatocytes [30]. …”
Section: The Hippo Pathway In the Development And Regeneration Of Difmentioning
confidence: 99%
“…In a model of liver injury, activating YAP via pharmacological inhibition of MST and MST2 improved liver repair and regeneration (12). YAP also determines the fate of injured hepatocytes, and YAP activation in undamaged hepatocytes leads to hepatocyte proliferation (13).…”
mentioning
confidence: 99%
“…We observed that PKA signaling and cytoskeleton remodeling occurred in both surrounding normal MDCK and YAP (5SA) cells during cell competition, but that E‐cadherin internalization took place only in YAP (5SA) cells. Previous reports have shown that the endocytosis of E‐cadherin is induced by the activation of the small GTP‐binding proteins CDC42 and Rac (Akhtar & Hotchin, ; Izumi et al, ) and that YAP activation induces the expression of various small GTP‐binding protein regulators such as ARHGAP18, ARHGAP29, Ect2 and Fgd3 (Miyamura et al, ; Porazinski et al, ; Qiao et al, ). We thus suggest that, in the presence of PKA‐promoted cytoskeleton remodeling, YAP‐driven regulation of small GTP‐binding proteins may trigger E‐cadherin internalization and thus induce apical extrusion specifically in YAP (5SA) cells.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse fibroblast NIH3T3 cells, cell competition resulting in apoptosis was reportedly dependent on TEAD activity (Mamada, Sato, Ota, & Sasaki, 2015). We subsequently showed that MDCK cells and mouse hepatocytes also undergo YAP-induced competition (Chiba et al, 2016;Miyamura et al, 2017). We generated doxycycline (Dox)-inducible YAP (5SA)-expressing MDCK cells [YAP (5SA) cells] and showed that they succumb to apical extrusion when surrounded by normal MDCK cells.…”
Section: Introductionmentioning
confidence: 99%